Adaptive Robust Control and Active Vibration Suppression of Dumbbell-Shaped Spacecraft. (8th September 2022) - Ai, Q. M.; Liu, T.; Fan, H. W.; Chen, J. M.; Li, S. L.
Abstract : In this paper, the dynamic modelling of a new configuration spacecraft is investigated. The significance of dumbbell-shaped spacecraft to deep space exploration and the configuration of dumbbell-shaped spacecraft are introduced firstly. Then, the vibration problem of the dumbbell-shaped spacecraft of large-angle attitude maneuver is investigated, and a control program based on the combination of adaptive robust control (ARC) and component synthesis vibration suppression method-seven-section path planning (CSVS-SPP) is proposed. The large-angle attitude maneuver route of the spacecraft, which serves as the reference path, is planned using the CSVS-SPP approach, and the attitude controller is designed using the ARC. This program can effectively reduce the influence of external disturbance and parameter uncertainty on the system performance while completing attitude maneuver and suppress the vibration of the flexible beam during large-angle attitude maneuver. The numerical simulations show the superiority and effectiveness of the proposed ARC+CSVS-SPP.